Results Characteristics of Lipid Profile Examination of Acute Ischemia Stroke Patients at RSUP Dr. Soedono Madiun, East Java - Wuryani, Dinik; Darumurti, Rissito Centricia (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Introduction: Dyslipidemia as reflected in the results of lipid profile examination is among the most common abnormalities found in acute ischemic stroke patients. Studies assessing the characteristic of these results may provide a foundation for an effective plan of treatment and prevention to overcome the burden of the disease.Objective: To study the characteristic of the results of lipid profile examination among acute ischemic stroke patients at Dr. Soedono General Hospital, Madiun, East Java.Methods: This research is a descriptive study with a cross-sectional approach using secondary data taken from the medical records of acute ischemic stroke inpatients at the Stroke Unit of Dr. Soedono General Hospital, Madiun, East Java admitted in January-December 2015. Results of lipid profile examination consisting of total cholesterol, LDL, HDL, and triglycerides were categorized as high, normal, and low based on their respective levels.Results: There were 72 subjects selected using simple random sampling. Level of total cholesterol was high in 52.78%, normal in 36.11%, and low in 11.11% of the subjects. Level of LDL was high in 54.17%, normal in 22.22%, and low in 23.61% of the subjects. Level of HDL was low in 31.94%, normal in 50.00%, and high in 18.06% of the subjects. Level of triglycerides was high in 26.39%, normal in 33.33%, and low in 40.28% of the subjects.Conclusion: Total cholesterol and LDL are generally high, HDL is generally normal, while triglycerides is generally low among acute ischemic stroke patients in Dr. Soedono General Hospital, Madiun, East Java.